Cost-benefit analysis in human resource management of construction projects using RFID technology - Alireza Hashemian; Roohollah Taherkhani; Mohammadali Nekooie (مهندسی و مدیریت ساخت)
One of the resources available in construction projects is human resources. The importance and influence of human resources in the success of projects on the one hand and the high costs caused by it in projects on the other hand have caused project managers to pay more attention to monitoring this resource and always look for new solutions and technologies to manage it. . In the meantime, one of the new technologies that has attracted the attention of various industries for this purpose is RFID technology. But the question that arises is, how can this technology help us? What capabilities does it have? Or when and what kind of projects this technology can be used effectively. In this regard, the present article aims to introduce this technology as an effective solution to the construction industry while examining the experiences of using this technology and answering these questions.